2020
DOI: 10.1111/aogs.13946
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum toxin injection for chronic pelvic pain: A systematic review

Abstract: Introduction: Botulinum toxin has proven therapeutic effects in alleviating pain in several myofascial disorders, with an expanding potential in chronic pelvic pain. The objective of this systematic review is to evaluate the efficacy and safety of botulinum toxin injection as an off-label treatment for female chronic pelvic pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…According to the literature, the most frequent adverse effects after BoNT/A infiltration are constipation, stress urinary incontinence, faecal incontinence and localized pain and/or bleeding from the injection site [10,14]. Unlike all the other studies published in the field [10], no adverse events were found after treatment, so that the protocol followed in the present study for BoNT/A infiltration can be regarded as a suitable option to improve the patients' clinical status while avoiding secondary effects.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…According to the literature, the most frequent adverse effects after BoNT/A infiltration are constipation, stress urinary incontinence, faecal incontinence and localized pain and/or bleeding from the injection site [10,14]. Unlike all the other studies published in the field [10], no adverse events were found after treatment, so that the protocol followed in the present study for BoNT/A infiltration can be regarded as a suitable option to improve the patients' clinical status while avoiding secondary effects.…”
Section: Discussionmentioning
confidence: 72%
“…The inability to know in advance whether the patient is a potential responder to botulinum toxin, as well as the absence of a significant improvement of CPP symptoms after treatment, can be frustrating for both the patient and the physician. A recent review on the use of the toxin to treat CPP suggested that factors such as concurrent pain conditions could significantly confound BoNT/A's effectiveness [14]. Nevertheless, no study has yet analyzed the influence of the patients' clinical characteristics and medical history on their response to this treatment in CPP.…”
Section: Introductionmentioning
confidence: 99%
“…Pain reduction in BoNT group was significantly greater than placebo Trigeminal neuralgia 1,5,27 Postherpetic neuralgia Phantom limb pain and residual limb pain 1,5 Case series and placebocontrolled RCT Both BoNT and placebo showed reduction of pain; no statistical difference noted Complex regional pain syndrome 5,[38][39][40] Case series and RCT Reduction of pain with BoNT injections…”
Section: Neuropathic Painmentioning
confidence: 99%
“…In a 2020 systematic review (including 12 observational studies and 5 randomized controlled trials) of BoNT for treatment of chronic pelvic pain, the quality of evidence varied widely. 38 Observational studies showed good benefit, but only 1 randomized trial showed statistical difference with the use of BoNT for pelvic pain. No serious adverse events were reported in any of the studies.…”
Section: Chronic Pelvic Painmentioning
confidence: 99%
See 1 more Smart Citation